Assessment of phonological awareness in second-language learners: the critical period and age effects. Annual Workshop on Bilingualism: Functional and neural perspectives - Figueiredo, Sandra (2018)
According to previous framework, the main factors which explain the second language learners differences are the linguistic knowledge, psychological and affective variables, gender, neuronal and cognitive maturation, and age. Related to the last factors, we find the critical period principle, and the effects are present both in first and second language acquisition contexts. The critical period explains how the youngest learners have more sucess with the languages acquisition, with several timings to reach the linguistic and metalinguistic levels. The phonological awareness, as one of many cognitive abilities, with processes, is a competence and also a cognitive space where the learner could grow to an accuracy level of phonological discrimination and processing. Is believed that after the critical period, several code levels fossilize suchs as the phonological code and phonetics identity, the ‘language processor’ (Klein, in Magnusson, 1996) declines. Here will be presented and discussed some results of our study, particullary regarding the phonemic blending and alliteration judgement skills.